1972
DOI: 10.1136/thx.27.4.463
|View full text |Cite
|
Sign up to set email alerts
|

Experience with mediastinoscopy

Abstract: Six hundred and eighty diagnostic mediastinoscopies are presented. Of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Such nodes, frequently associated with post-inflammatory adhesions in the interlobar fissures, must be carefully considered before performing Video-Assisted Thoracoscopic Surgery (VATS) or thoracotomy for lymph node biopsy in the absence of parenchymal lesions (32). Cervical mediastinoscopy plays a marginal role in the diagnosis of mediastinal TB since the proportion of patients benefitting from this procedure is considerably limited (33,34). Sayar et al reported a series of 19 patients with no parenchymal abnormalities who underwent mediastinoscopy and TB was confirmed in 16 of them.…”
Section: Diagnosis Of Complicated Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such nodes, frequently associated with post-inflammatory adhesions in the interlobar fissures, must be carefully considered before performing Video-Assisted Thoracoscopic Surgery (VATS) or thoracotomy for lymph node biopsy in the absence of parenchymal lesions (32). Cervical mediastinoscopy plays a marginal role in the diagnosis of mediastinal TB since the proportion of patients benefitting from this procedure is considerably limited (33,34). Sayar et al reported a series of 19 patients with no parenchymal abnormalities who underwent mediastinoscopy and TB was confirmed in 16 of them.…”
Section: Diagnosis Of Complicated Casesmentioning
confidence: 99%
“…If bronchoscopic biopsies failed to confirm diagnosis, video-assisted thoracoscopy or mediastinoscopy are valid alternatives. Diagnostic thoracotomy is rarely necessary, but may be considered in selected cases (30,(33)(34)(35)(36)(37)(38). (III) In MDR-TB patients, surgical resection of pulmonary bacillary lesions may be useful to improve treatment outcome if chemotherapy failed, but before complete destruction of lung parenchyma and associated decline in pulmonary function (16,41,44,48,49,99).…”
Section: (Ii)mentioning
confidence: 99%
“…In a combined series of 4,953 patients with primary bronchial carcinoma, positive mediastinal biopsies were obtained in 39% of cases (Jepson and Rahbek, 1970). In more recent series, 2848% of presumably operable patients have yielded positive mediastinal biopsies (Ashraf et al, 1980;Fishman and Bronstein, 1975;Gibbons, 1972;Kirschner, 1971;Larsson, 1976;Otto, Zaslonska and Lukianski, 1972), this proportion representing 80-90%7o (sensitivity) of all patients found to have mediastinal disease at thoracotomy (Jepson and Rahbek, 1970;Larsson, 1976;Pearson, 1968;Pearson et al, 1972). Positive findings, as denoted by the presence ofpathologically identifiable tumour in mediastinal biopsies, provide a highly specific diagnosis and for practical purposes the specificity of mediastinoscopy can be assumed to be 100%.…”
Section: Mediastinoscopy and Mediastinotomymentioning
confidence: 99%